2012
DOI: 10.1093/cid/cis213
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Colonization Among Household Contacts of Patients With Skin Infections: Risk Factors, Strain Discordance, and Complex Ecology

Abstract: Background. The USA300 methicillin resistant Staphylococcus aureus (MRSA) genetic background has rapidly emerged as the predominant cause of community-associated S. aureus infections in the U.S. However, epidemiologic characteristics of S. aureus household transmission are poorly understood.Methods. We performed a cross-sectional study of adults and children with S. aureus skin infections and their household contacts in Los Angeles and Chicago. Subjects were surveyed for S. aureus colonization of the nares, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(143 citation statements)
references
References 58 publications
6
134
2
1
Order By: Relevance
“…None of his 4 household contacts and no other subject in our study of 350 households was colonized with an MSSA or MRSA ST398 isolate (24). As determined by PFGE, ST398 isolates from the Dallas County Jail, from New York State Prisons (30), from the patient in Chicago, and from northern Manhattan (22) all shared PFGE patterns with Ͼ80% identity by Dice coefficient analysis (Fig.…”
mentioning
confidence: 83%
“…None of his 4 household contacts and no other subject in our study of 350 households was colonized with an MSSA or MRSA ST398 isolate (24). As determined by PFGE, ST398 isolates from the Dallas County Jail, from New York State Prisons (30), from the patient in Chicago, and from northern Manhattan (22) all shared PFGE patterns with Ͼ80% identity by Dice coefficient analysis (Fig.…”
mentioning
confidence: 83%
“…Indeed, many individuals with colonization in the throat or on the skin over the inguinal area have no colonization in the nasopharynx (5)(6)(7)(8). Small studies in the United States and elsewhere have demonstrated that S. aureus, and specifically the methicillin-resistant S. aureus (MRSA) genetic background USA300 can be found elsewhere on the body (reviewed in reference 4).…”
mentioning
confidence: 99%
“…In this study, 30 of the 55 (54.5%) S. aureus isolates were PVL-positive. Miller et al (3) in Torrance, California, also reported high PVL positivity (76%) in S. aureus causing SSTIs. However, other reports employing the same criteria showed lower prevalences of 15.1%, 15.79%, and 41.46% in Brazil, Egypt, and China, respectively (15,17,18).…”
Section: Discussionmentioning
confidence: 92%
“…Carriage of S. aureus is a risk factor for subsequent infection in various settings. Recent investigations suggest that nares-only screening may underestimate the prevalence of S. aureus colonization, and accurate determination requires sampling from other body sites (3). The spread of antibiotic resistance among strains of S. aureus has been dramatically elevated, such that methicillin-resistant S. aureus (MRSA) is recognized as a nosocomial pathogen worldwide.…”
Section: Introductionmentioning
confidence: 99%